Entertaining Byron in America. Issue 1 (June 2017) - Wolfson, Susan J.
Abstract : If Byron did not get to America in the flesh, he was everywhere in formation. Editions and portraits, low-market to sumptuous, were rife in bookshops. Aspiring poets bid for the title of 'American Byron', or short of this, displayed Byron, in allusions, literary style, and social affectation. This essay discusses some of the most intriguing landmarks, beginning with early imitators and the public debates about the values of Byronism for American national identity. One emanation is Adah Isaacs Menken's spectacular performance as the title character of Mazeppa . Another is a Victorian-era parlour conjuring of Byron, from the recipe of his famous portraits, his stylistic signatures and his biography. The essay rounds into a tour of 'Byron'-named sites on the American landscape from his day to ours, and comes to a conclusion with the resurrection of a famously lost piece of Byroniana at a church bazaar in Savannah, Georgia. 1